Histopathological of White Rats Aorta Induced by High-Fat Feed After Administered by Neem Leaf Ethanolic Extract - Baiq Miftahul Jannah; Sri Isdadiyanto; Agung Janika Sitasiwi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Neem (Azadirachta indica A. Juss) is one of the traditional medicines used by local people as antioxidants, anti-hyperlipidemia, anti-inflammatory, and treatment for other diseases such as heart disease. This study aimed to analyze the effect of neem leaf ethanolic extract on aortic wall thickness and aortic lumen diameter of white rats induced by high-fat feed. The male Wistar rats (Rattus norvegicus L.) with 2 months of age were used. This research was an experimental study with a Randomized Complete Block Design consisted of 6 treatments (P0: commercial feed, P1: high-fat feed and duck egg yolk 2.5 ml/200 g BW per oral, P2: P1 + 8 mg/200 g BW simvastatin, P3-P5: P1+ neem leaf extract of 75, 100, and 125 mg/200 g BW respectively) and 4 replications. Aortic preparations were made by the paraffin method and Hematoxylin-Eosin staining. Data were analyzed using ANOVA followed by Duncan Multiple Range Test with 95% confidence level. The result showed that the decrease in wall thickening and lumen narrowing was getting higher along with the increasing doses of ethanol extract of neem leaves. Based on the result of this research, it was found that the high doses of neem leaf ethanolic extract has the same ability with simvastatin to reduce aortic wall thickning and aortic lumen narrowing of white rats. This study is give a new information that the neem leaves can be used as an alternative medicine for cardiovascular disease.